1955
DOI: 10.1111/j.1748-1716.1955.tb01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Pulmonary Ventilation during Rest and Light Exercise. A Study of Alveolar Nitrogen Wash‐out Curves in Normal Subjects.

Abstract: Summary. The ventilatory efficiency has been studied at rest and during exercise in 9 normal subjects. For light and moderate degrees of work the relative efficiency is the same as at rest. This conclusion is based upon determination of the pulmonary nitrogen clearance delay percentage (Fowler) and of the lung clearance index (Becklake); the latter is the more dependable of the two indices. The wash‐out time, i.e. the time it takes to wash out the pulmonary nitrogen from 80% down to 2%, decreases with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1959
1959
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 6 publications
0
15
0
1
Order By: Relevance
“…Wash-out volume (WOV) and lung clearance index (LC1) were measured with a nitrogen wash-out method [6].…”
Section: Methodsmentioning
confidence: 99%
“…Wash-out volume (WOV) and lung clearance index (LC1) were measured with a nitrogen wash-out method [6].…”
Section: Methodsmentioning
confidence: 99%
“…Static lung volumes were measured with a Knipping spirometer [15] and dynamic lung volumes with a Bernstein spirometer [4]. Wash-out volume (WOV) and lung clearance index (LCD were measured with a nitro gen wash-out method [5]. Arterial blood samples were obtained in the supine position in all subjects and after arterial catheterization (PE 160), in the last 7 also in the sitting, during exercise, and in the right and left lateral recumbent positions.…”
Section: Methodsmentioning
confidence: 99%
“…The graphic analysis of the nitrogen washout curves [4,8,18] showed that in all patients the behavior of the nitrogen clearance could be described on the basis of a nonuniform lung model consisting of a more or less poorly venti lated compartment, or slow space (with ventilation, per unit lung volume, VAs/U and relative volume Ls/L t and 1-3 better ventilated compartments). Mean values for VAs/L s and Ls/ L j are presented in table II.…”
Section: Resultsmentioning
confidence: 99%
“…Various indexes have been proposed to quantify the degree of gas distribution in equality and its impact on overall effi ciency of ventilation [17]. Some of these indexes are based on very simple criteria; in this category the lung clearance index (LCI), essentially a measure of the effi- ciency of the washout process, has most commonly been used in various versions [1,4,10,25]. The graphic analysis of the nitrogen washout curves [18] provides quantitative gas distribution data on the basis of a simple lung model consisting of a very limited number of compartments.…”
Section: Introductionmentioning
confidence: 99%